2013
DOI: 10.1111/gcb.12397
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the viability of sea turtle eggs in a warming world

Abstract: Animals living in tropical regions may be at increased risk from climate change because current temperatures at these locations already approach critical physiological thresholds. Relatively small temperature increases could cause animals to exceed these thresholds more often, resulting in substantial fitness costs or even death. Oviparous species could be especially vulnerable because the maximum thermal tolerances of incubating embryos is often lower than adult counterparts, and in many species mothers aband… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 50 publications
(142 reference statements)
5
76
0
1
Order By: Relevance
“…Increasing evidence suggests that many reef fish species are already living close to their thermal optima (Rummer et al 2014), meaning that that higher ocean temperatures will lead to reduced fitness or mortality (Munday et al 2008). Many marine species, ranging from turtles to phytoplankton, have altered their distributions in response to warming waters in order to maintain their optimal thermal range (Polovina et al 2008;Pike 2014). These relocations Organizational networks and bridging social capital may lead to local extinctions of fish populations, new species interactions and profound changes in marine food webs (Mueter and Litzow 2008).…”
Section: Climate Change Relatedmentioning
confidence: 99%
“…Increasing evidence suggests that many reef fish species are already living close to their thermal optima (Rummer et al 2014), meaning that that higher ocean temperatures will lead to reduced fitness or mortality (Munday et al 2008). Many marine species, ranging from turtles to phytoplankton, have altered their distributions in response to warming waters in order to maintain their optimal thermal range (Polovina et al 2008;Pike 2014). These relocations Organizational networks and bridging social capital may lead to local extinctions of fish populations, new species interactions and profound changes in marine food webs (Mueter and Litzow 2008).…”
Section: Climate Change Relatedmentioning
confidence: 99%
“…The effects of temperature on life history can vary with life stage, such that adult and embryonic stages have different habitat requirements and physiological tolerances (Telemeco et al, 2013a;Howard et al, 2014;Pike, 2014). In these instances, the embryonic stages of oviparous species, which often do not provide parental care during incubation, may be most vulnerable to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The embryonic stage of sea turtles must occur on land because the amniotic eggs need to exchange gas across the shell membrane to survive through to hatching (Ewert, 1985). Because eggs are in the nest for long periods before hatching (∌50-65 days), the effects of climate change are anticipated to be most dramatic during this phase of their life history (Hawkes et al, 2009;Fuentes et al, 2011;Pike, 2014). Warmer nest temperatures could therefore lead to reductions in hatching success, and if temperatures rise above the pivotal sex-determining temperature, the feminisation of hatchling sex output (reviewed by Jourdan and Fuentes, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Janzen (1993) determined that hatchling size and fitness are affected by high incubation temperatures; as a result, Glen et al (2005) suggested that hatchlings developed in high-temperature environments are less vigorous. Pike (2014) indicated that changes in nest temperatures might significantly alter hatchling phenotypes. In summary, because temperature in Guanahacabibes is rising and loggerhead hatchlings are becoming smaller, it is quite possible that the fitness of the offspring that have been produced in those beaches has been compromised, and this could increase mortality in the first stages.…”
Section: Discussionmentioning
confidence: 99%